2005
DOI: 10.1007/s00115-004-1790-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in multiple sclerosis

Abstract: Measuring quality of life (QOL) has made essential contributions for the management of patients with multiple sclerosis (MS). QOL measures may be used for helping to assess the complex changes which patients with MS have to go through during the disease trajectory, and they may be used for pharmacoeconomic research. The large number of tests available includes generic ones such as Short Form SF-36 and Sickness Impact Profile, health-related ones such as MSQOL-54, FAMS, or HAQUAMS, and patient generated measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 111 publications
(69 reference statements)
1
4
0
Order By: Relevance
“…In the present study, quantitative analysis using effect sizes revealed the greatest differences in the dimensions anxiety, physical functioning, role-physical functioning and general health. This finding underscores the importance of psychological, 3 social and impairment-related aspects, 8 , 10 and their interrelation in patients with MS. 7 , 23 , 24 With respect to a few HRQoL dimensions, our data confirm results from other countries, but also deliver a specific pattern of impaired HRQoL. In detail, mental health was the only dimension that was not affected in our cohort of MS patients.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In the present study, quantitative analysis using effect sizes revealed the greatest differences in the dimensions anxiety, physical functioning, role-physical functioning and general health. This finding underscores the importance of psychological, 3 social and impairment-related aspects, 8 , 10 and their interrelation in patients with MS. 7 , 23 , 24 With respect to a few HRQoL dimensions, our data confirm results from other countries, but also deliver a specific pattern of impaired HRQoL. In detail, mental health was the only dimension that was not affected in our cohort of MS patients.…”
Section: Discussionsupporting
confidence: 57%
“… 8 Health-related quality of life (HRQoL) can be considered as a multidimensional index of well-being that involves the individual patient's perspective. 8 10 Previous studies have assessed HRQoL in MS patients in comparison to the general population, which have resulted in inconsistent reports. For example, one study found worse scores for physical functioning, vitality and general health in a cohort of 185 MS patients in the US, but also domains that were similar to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…The SEIQoL-DW index is obtained from the satisfaction with and weighting for each area, and ranges from 0 (worst possible score) to 100 (best possible score). SEIQoL-DW has been used in neurological diseases [ 27 - 30 ], and was the primary outcome measure of the Ne-Pal trial [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…CBTs treatments showed a positive short-term effect on fatigue, even if the proposals, the outcomes and the results are still very heterogeneous [ 17 , 32 , 33 ]. We did not find a consistent change of QoL in pwMS, probably due to the high variability of the sample, the dissociation between the two scores [ 34 , 35 ] or because IID could not help enough to cope with MS. PwINS reported a significant improvement on cognitive fatigue, the highest at baseline. A durable benefit was noticed on sleep as well as on psychological stress and QoL.…”
Section: Discussionmentioning
confidence: 71%